Health effects of job insecurity - Francis Green (IZA World of Labor, 2015)
Research has shown that job insecurity affects both mental and physical health, though the effects are lower when employees are easily re-employable. The detrimental effects of job insecurity can also be partly mitigated by employers allowing greater employee participation in workplace decision-making in order to ensure fair procedures. But as job insecurity is felt by many more people than just the unemployed, the negative health effects during recessions are multiplied and extend through the majority of the population. This reinforces the need for more effective, stabilising macroeconomic policies.
Keywords: I10; J00; J08; 330; job insecurity; employability; unemployment